Electrochemical modulation of annealed steel via cupric sulfate, potassium chloride and trisodium citrate: insights into redox behaviour and corrosion resistance - Francisco Augusto Nuñez Perez (Journal of Electrochemical Science and Engineering)
This study probes the electrochemical modulation of annealed steel in 0.01 M copper sulfate (CuSO₄) solutions with potassium chloride (KCl) and trisodium citrate additives, using cyclic voltammetry, electrochemical impedance spectroscopy and chronoamperometry. A three-electrode system, annealed steel wire, Ag/AgCl reference and Pt counter electrode, evaluated pure CuSO₄, CuSO₄ with 0.01 M KCl and CuSO₄ with 0.01 M trisodium citrate. KCl amplifies current density by 123 % and reduces charge transfer resistance by 75 % at -0.8 V vs. Ag/AgCl, enhancing copper electrodeposition kinetics. Trisodium citrate, forming Cu²⁺ complexes, curtails redox activity by 51 % and elevates polarization resistance at -0.6 V, fostering passivation. Measurements at -0.6 and -0.8 V highlight kinetic dominance of KCl and stabilizing effect of citrate ions, slashing corrosion rates from 154.87 to 8.05 mm year-1. These insights make a framework for corrosion-resistant coatings without reliance on structural imaging, with broad implications for electrochemical applications.